2014
DOI: 10.1111/jfpp.12405
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Textural Properties of Konjac Gels Formed with κ-Carrageenan or Xanthan and Xylitol as Ingredients in Jelly Drink Processing

Abstract: The effects of two independent variables: the ratio of konjac and secondary gum (κ-carrageenan or xanthan) (25:75 to 50:50) and the xylitol concentration (2-20%) on the textural properties (hardness, cohesiveness and springiness) of konjac gels were investigated using response surface methodology (RSM). Both independent variables had a significant effect on konjac gel texture, but their interactive effects were insignificant. The konjac/secondary gum ratio had a greater effect, and it affected konjac gel textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…The study showed that konjac mannan-κ-carrageenan-locust bean gum gels with greater fracture strain and work required more mastication effort and less swallowing effort than agar gels with higher elastic modulus [ 62 ]. The effects of two different gums (κ-carrageenan or XG) and the xylitol concentration on the textural properties of KGM gels were investigated using response surface methodology by Akesowan [ 63 ], The KGM gels optimal conditions were used to product no added sugar, 20% grape juice jelly drinks. The study showed that the KGM jelly drinks containing κ-carrageenan were more acceptable and achieved a higher consumer purchase rate than those containing XG.…”
Section: Application Of Kgm Gelmentioning
confidence: 99%
“…The study showed that konjac mannan-κ-carrageenan-locust bean gum gels with greater fracture strain and work required more mastication effort and less swallowing effort than agar gels with higher elastic modulus [ 62 ]. The effects of two different gums (κ-carrageenan or XG) and the xylitol concentration on the textural properties of KGM gels were investigated using response surface methodology by Akesowan [ 63 ], The KGM gels optimal conditions were used to product no added sugar, 20% grape juice jelly drinks. The study showed that the KGM jelly drinks containing κ-carrageenan were more acceptable and achieved a higher consumer purchase rate than those containing XG.…”
Section: Application Of Kgm Gelmentioning
confidence: 99%
“…On the other hand, several studies indicate that sensory properties of beverages, gels and soups (odour, flavour and taste) decrease as a result of the addition of hydrocolloids (Ibrahim et al, ; Pangborn, Gibbs, & Tassan, ; Walker & Prescott, ; Will et al, ). In some cases, different effects of several used hydrocolloids on sensorial parameters of beverages have been found (Akesowan, ). The aim of many studies was the comparison of juices with different hydrocolloids with each other but not with the original (not thickened) juice; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pektin dan gula perlu disiapkan dengan perbandingan yang cermat karena sangat mempengaruhi kualitas dari minuman jelly (Nazir dan Adrian, 2016). Salah satu contoh pektin yang digunakan adalah karagenan, yang fungsinya adalah sebagai pembentuk jelly (gelling agent) (Akesowan, 2015). Penambahan karagenan akan membentuk struktur jelly yang cenderung elastis dan kenyal sehingga dihasilkan minuman jelly yang kental dengan tekstur yang mantap, namun bentuk gel-nya masih terasa di mulut, dan dapat disedot dengan mudah (Widawati dan Hardiyanto, 2016).…”
Section: Paramater Teknisunclassified
“…Menurut Agustin dan Putri (2013) kekentalan jelly sangat dipengaruhi oleh bahan baku pembuatannya yaitu karagenan. Karagenan merupakan senyawa hidrokoloid yang dapat berfungsi sebagai pembentuk gel, bahan pengental, stabilizer serta emulsifier, sehingga penambahan karagenan dapat mempengaruhi viskositas dan tekstur minuman jelly (Akesowan, 2015). Karagenan dapat membentuk struktur gel yang cenderung elastis dan kenyal (Widawati dan Hardiyanto, 2016).…”
Section: Paramater Teknisunclassified